The process of microRNAs discovery - Kawalec, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
The widespread particularist account of the onset of molecular biology that identifies it with the discovery of the DNA structure in 1953 has been recently contested. The paper contributes to this debate by focusing on a more recent discovery of small noncoding RNAs (microRNAs). First, it outlines a particularist account of the microRNAs discovery and the origins of the particularist predilection of the modern scientometric studies of science dynamics. Next, it discusses its limitations and proposes an alternative, modified processualist account of the discovery. In the final part, the paper applies this approach to unravel network dynamics of the research on the first two microRNAs that were discovered, namely lin-4 and let-7.
Keywords: breakthrough research; let-7; lin-4; particularism; processualism; scientific discovery; research routine; microRNAs; noncoding RNA